FORMULATION, IN-VITRO&IN-VIVO EVALUATION OF NANOEMULSION GEL FOR TRANSDERMAL DRUG DELIVERY OF NIMODIPINE - Yadav, Sheela A; Poddar, Sushilkumar S (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: The objective of this study was to develop and evaluate the potential of nanoemulsion (NE) as drug carrier system for transdermal delivery of nimodipine. Methods: Nimodipine NE was developed through titration method. This was then formulated in to gel. Transdermal in-vitro permeation of nimodipine through wistar rat abdominal skin was determined with Franz diffusion cell. The in-vitro skin permeation profile of optimized formulation was compared with NE gel (NEG), control or drug loaded neat components. Result: Significant increase in the steady state flux (Jss), permeability coefficient (kp) and enhancement ratio was observed in the NE formulation and were compared with other formulations. The highest value of the permeability coefficient was obtained in the optimized NE formulation consisting of 0.008% w/w of nimodipine, 8.00% w/w of triacetin:isopropyl myristate (1:1), 32.00% w/w of Smix (2:1 Tween 80 and PEG-400) and 60.00% w/w of distilled water. The bioavailability studies in wistar rat showed about 3 times improvement for transdermal administration of NEG compared with an oral suspension. The present work also evaluated the transdermal product on blood pressure of methyl prednisolone acetate induced hypertensive rats. Conclusion: The results of the present investigation suggested that NE could be a potential vehicle for improved transdermal delivery of nimodipine. Keywords: Nimodipine, Nanoemulsion, Gel, Transdermal delivery, Anti-hypertensive.